1988
DOI: 10.1111/j.1476-5381.1988.tb11435.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between extracellular 5‐hydroxytryptamine and behaviour following monoamine oxidase inhibition and l‐tryptophan

Abstract: 1 The present study investigates the effects of selective and a non-selective monoamine oxidase (MAO) inhibitors combined with L-tryptophan on MAO-A and -B activity, hypothalamic extracellular 5-hydroxytryptamine (5-HT) in vivo and the occurrence of the 5-HT behavioural syndrome.2 Selective inhibition of intraneuronal MAO-A with MDL 72394 (0.5 mg kg-', i.p.) had no effect on extracellular 5-HT and following administration of L-tryptophan (50mg kg-', i.p.) the 5-HT behavioural syndrome was not induced. 3 Select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Almost all research on L-Trp-related effects during these years has been focused on the synthesis and the release of serotonin by serotonergic neurons and on the Trp-induced modulation of 5-HT- In spite of all these efforts, the controversity still persists whether or not functional serotonergic activity is actually stimulated by L-Trp. In microdialysis experiments 5-HT release is found to be enhanced by L-Trp by some authors (Carboni et al 1989;Schwartz et al 1990) but not by others (Sleight et al 1988). One study shows that this release is tetrodotoxin-sensitive and Ca + ÷ -dependent (Carboni et al 1989), but electrical stimulation of hippocampal slices failed to enhance the Trp-induced 5-HT release in another study (Schaechter and Wurtman 1990).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Almost all research on L-Trp-related effects during these years has been focused on the synthesis and the release of serotonin by serotonergic neurons and on the Trp-induced modulation of 5-HT- In spite of all these efforts, the controversity still persists whether or not functional serotonergic activity is actually stimulated by L-Trp. In microdialysis experiments 5-HT release is found to be enhanced by L-Trp by some authors (Carboni et al 1989;Schwartz et al 1990) but not by others (Sleight et al 1988). One study shows that this release is tetrodotoxin-sensitive and Ca + ÷ -dependent (Carboni et al 1989), but electrical stimulation of hippocampal slices failed to enhance the Trp-induced 5-HT release in another study (Schaechter and Wurtman 1990).…”
Section: Discussionmentioning
confidence: 90%
“…In rats pretreated by monoamine oxidase inhibitors a marked increase of brain tryptamine levels resulted from L-Trp administration, which was proportionally greater than that of 5-HT (Marsden and Curzon 1978). Such treatments elicit a so-called 5-HT behavioral syndrome, which is more likely a result of the accumulation of tryptamine than of extracellutar 5-HT (Marsden and Curzon 1979;Sleight et al 1988). The possible role of tryptamine as a modulator of monoaminergic neurotransmission has recently been reviewed (Juorio and Paterson 1990).…”
Section: Discussionmentioning
confidence: 97%
“…The concentration of 5-HT in the brain extracellular space depends on different factors, such as the firing rate of serotonergic neurones (Sharp et al, 1990), the activity of monoamine oxidase (Sleight et al, 1988;Celada and Artigas, 1993), and the function of the antidepressant-sensitive 5-HT uptake system (for review see Fuller, 1994;Artigas et al, 1996). Previous studies indicated that, in absence of pharmacological interventions, the extracellular concentration of 5-HT in different areas of the rat brain is confined within a relatively narrow range and does not reflect that present in brain tissue Jackson and Abercrombie, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…After each of the various protocols listed in Table 1 (experiment 1), the barrel field was examined with Nissl and CO stains at P8. We started with a 5 mg/kg daily injection of clorgyline, a dose that is known to acutely inhibit MAOA activity by nearly 100% in adult rats and that does not produce obvious behavioral alterations (Green and Youdim, 1975;Sleight et al, 1988). After daily administrations from E15 to P7, a few abnormally shaped barrels were observed in CO-stained coronal sections (4 of 14 pups).…”
Section: Optimization Of Clorgyline Dosage Regimementioning
confidence: 99%